Dentists' skills with fearful patients: education and treatment. (19th January 2013) - Brahm, Carl‐Otto; Lundgren, Jesper; Carlsson, Sven G.; Nilsson, Peter; Hultqvist, Johanna; Hägglin, Catharina
Abstract : The aims were to explore dentists' skills in dental fear, current strategies when treating fearful adult patients, and the possible need for additional education among dentists working in Sweden. A sample of 1, 293 members of the Association of Public Health Dentists in Sweden were asked to respond to a Web survey concerning dental fear. The response rate was 69% ( n  =   889); 91% trained in Sweden and 9% trained in another country. The most frequently used pharmacological anxiety‐reducing techniques were medication with a midazolame mixture (72%) and benzodiazepine tablets (77%), and the most commonly used psychological techniques were relaxation (68%), distraction (66%), and Tell‐Show‐Do (86%). A larger proportion of dentists trained in Sweden, compared with dentists who were trained in other countries, reported that they had received undergraduate training in dental fear. Dentists trained in Sweden more often reported competence in pharmacological and psychological anxiety‐reducing techniques, compared with dentists who were trained in other countries. Higher levels of self‐rated efficacy in treating fearful patients accompanied additional education in dental fear after graduation. In conclusion, Swedish dentists use a variety of techniques to meet the needs of fearful dental patients. Competence in anxiety‐reducing techniques is associated with self‐efficacy and the site of education.